Prior response to infliximab and early serum drug concentrations predict effects of adalimumab in ulcerative colitis. Issue 11 (2nd October 2014) - Baert, F.; Vande Casteele, N.; Tops, S.; Noman, M.; Van Assche, G.; Rutgeerts, P.; Gils, A.; Vermeire, S.; Ferrante, M.
Summary: Background: Data for adalimumab in ulcerative colitis after prior use of infliximab are scarce. Aims: To study adalimumab response rates and predictors of response in ulcerative colitis, including drug concentrations. Methods: In this single centre cohort study 73 UC patients, previously exposed to infliximab, were assessed for response to adalimumab at weeks 12 and 52. Serum samples prior to week 12 were available and included in multivariate analysis to predict response. Results: Overall clinical response at week 12 and 52 were 75% and 52%, respectively. Adalimumab was continued without need for dose escalation throughout year 1 in 16 patients, 22 needed dose escalation and 35 discontinued treatment within 1 year. Prior response to infliximab and early serum concentrations correlated with response. Receiver operator characteristic curve analysis yielded optimal adalimumab concentrations of 4.58 μg/mL for week 12 and 7.0 μg/mL for week 52. Independent predictors for response at week 12 were primary response to infliximab [odds ratio (OR) 8.33; 95% confidence interval (CI) 1.8–33.3; P = 0.006] and an adalimumab concentration ≥4.58 μg/mL at week 4 (OR 4.85; 95% CI 1.3–18.6; P = 0.009). Positive predictors for week 52 response were primary response to infliximab (OR 5.2; 95% CI 1.14–23.8; P = 0.034) and adalimumab concentration at week 4 of ≥7 μg/mL (OR 3.56; 95% CI 1.17–10.79; P = 0.025). Conclusion: Prior response to infliximab and high early adalimumab serum concentrations predict week 12 and year 1 responses to adalimumab in ulcerative colitis.